PERILAKU MEMILIH GENERASI MUDA KELUARGA ANGGOTA POLRI DALAM PEMILIHAN GUBERNUR JAWA TENGAH 2013 - Radityo Pambayun; D Ghulam Manar; Purwoko . (Journal of Politic and Government Studies, 2014)
ABSTRACTThis study aims to determine the voting behavior in the Police family during Central Java Governor election 2013. This study used qualitative of research methods. Techniques of data collection using semi-srtuctural interviews that use open-ended questions, based on the interview guide. The results showed if family Indonesian Police is critical voters because they determine choice Governor of Central Java based on the candidate's ability, experience and political career bearer candidates and political party of candidates.Keywords: Central Java Governor Election 2013, Voter Critical, Choosing Behavior